Pengaruh Kecerdasan Emosional Guru PAK Terhadap Pembentukan Karakter Siswa Kelas V SD Negeri 173299 Paniaran Tahun pembelajaan 2023/2024 - Indah Rohani Sihombing; Damayanti Nababan; Lince R.T Simamora; Taripar Aripin Samosir; Maryska Debora Silalahi (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The aim of this research is to find out how much influence the Emotional Intelligence of Christian Religious Education Teachers has on the character formation of Class V Students at SD 173299 Paniaran for the 2023/2024 academic year. The research method used is a quantitative method with descriptive statistics. The population is all class V students of SD 173299 Paniaran who are Protestant Christians with a total of 32 people and this research is a population research. Data was collected using a positive closed questionnaire with 37 items, namely 15 items for variable : 1) Test the analysis requirements: a) positive relationship test obtained rxy = 0.585 > rtable(=0.05,n=32) = 0.349. b) Testing a significant relationship obtained tcount= 3.946 > ttable(=0.05, dk=n-2=30)= 2.042. 2) Test the effect: a) Test the regression equation, obtained the regression equation Y=21.17+1.06X. b) Regression coefficient of determination test (r2) = 34.2%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(=0.05, dk numerator k=13, dk denominator=n-2=32-2=30) namely 15.56 > 2.09. Thus Ha is accepted and H0 is rejected.